2009
DOI: 10.4161/cbt.8.11.8531
|View full text |Cite
|
Sign up to set email alerts
|

A novel antibody fragment targeting HAb18G/CD147 with cytotoxicity and decreased immunogenicity

Abstract: [ 131 I]Metuximab injection (Licartin) was an efficient therapeutic anti-hepatocellular carcinoma (HCC) radioimmunological agent generated by labeling 131 I with the murine monoclonal antibody fragment HAb18-F(ab') 2 but human anti-mouse antibody (HAMA) response in some patients after administration limited its clinical use. To reduce the immunogenicity of murine antibody, we attempted to humanize HAb18 by variable domain resurfacing based on the three-dimensional structure of Fv fragment. Considering the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The enhanced anti-tumor surveillance could also be obtained by functional antibody blocking of CD147 in both the melanoma and orthotopic models of liver cancer. CD147 is an established target for antibody-mediated cancer therapy, and its clinical efficacy was attributed to the direct blockade of CD147 signaling in tumor cells (Wang et al, 2015) and antibody-dependent cell-mediated cytotoxicity (Zhu et al, 2009). However, in our animal models, the efficacy of anti-CD147 therapy also seems to rely on the presence of NK1.1 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced anti-tumor surveillance could also be obtained by functional antibody blocking of CD147 in both the melanoma and orthotopic models of liver cancer. CD147 is an established target for antibody-mediated cancer therapy, and its clinical efficacy was attributed to the direct blockade of CD147 signaling in tumor cells (Wang et al, 2015) and antibody-dependent cell-mediated cytotoxicity (Zhu et al, 2009). However, in our animal models, the efficacy of anti-CD147 therapy also seems to rely on the presence of NK1.1 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was approved by SFDA for use in hepatic artery interventional embolization to treat HCC. Analyses of its RIT mechanisms revealed that I 131 ‐mab binds to the HAb18G/CD147 antigen on HCC cell surface, thereby blocking this target molecule, abolishing downstream signal transduction and suppressing tumor proliferation and metastasis (Xu et al., 2007; Zhu et al., 2009). Meanwhile, the antigen–antibody binding was shown to result in the targeted delivery of radioactive I 131 to cancer tissues, whereby I 131 releases beta and gamma rays to directly kill cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these antibody therapeutic candidates are derived from classical hybridoma technology. To reduce immunogenicity in humans, these mouse monoclonal antibodies are often humanized (Alegre et al, 1992;Hsu et al, 1999;Zhu et al, 2009). The development of human antibody-based phage display libraries and human immunoglobulin transgenic mice has allowed the discovery of human antibodies (Hudson & Souriau, 2001;Kotlan & Glassy, 2009).…”
Section: Antibody-base Approaches As Drugs Themselvesmentioning
confidence: 99%